Memorable tourism experience research: a systematic review of the literature. - Hosseini, Seyedassad; Cortés-Macías, Rafael; Almeida-García, Fernando (Routledge, 2023)
In recent years, the issue of memorable tourism experience (MTE) has garnered increasing attention from scholars and tourism practitioners. This paper provides a systematic review of 52 articles on MTE listed on the SCOPUS and WOS databases from 2012 to 2020. Qualitative analysis of the literature identified nine main categories of topics in MTE-related articles. Results showed that the largest proportion of articles focused on how MTEs influenced tourists’ perceptions and behaviours and how they shaped destination marketing. Co-occurrence analysis was performed to investigate trends in the keywords used by academics over the past f ive years. The geographic location of studies, research methods and theories applied in these articles were also analysed. Most articles were published in the current decade and China was the geographic setting for the highest number of articles in the review. The review concludes with the theoretical and practical implications of the study as well as the directions for future research.
Keywords: Turismo; Investigación cualitativa; Memorable tourism experience; Tourist experience; Memorability; Systematic review; Qualitative analysis